VALIDITAS DAN RELIABILITAS INSTRUMEN TES MATEMATIKA DASAR YANG BERKAITAN DENGAN PENDAHULUAN FISIKA INTI - Cecil . (Universitas Sriwijaya, 2015)
Development research test instrument math base on introduction nuclear physics lecture has been done. The method used is quantitative descriptive stages as follows: (1) Review basic math content that is relevant to the related nuclear physics through the study of literature; (2) Prepare draft test instruments with reference to the objectives, competence standard, basic competence, and indicators of achievement of design lectures were arranged; (3) Ask the expert assessment (validation construction and content); (4) To test the test instrument in a limited scope, evaluate and improve the existing deficiencies. The amount of matter that is developed in this test is 30 grains form the description. Data analysis test results of this test instruments in the group of students showed that the validity criteria are high, which is equal to 0.77. The instrument reliability was 0.87 which included a very high category. This means the resulting product meets the decent criteria, because validan reliable, but there are still items that need revision based on suggestions and feedback from the validator.